ALGAE AND PET APPLICATION IN THE DESIGN OF COMPONENTS FOR THE CAR INTERIOR - Lemos, Ana Francisca Portela de (2022)
Like many other companies in the automotive industry, TMG automotive tries to adapt the sustainability theme in every department involved in the production. The raw materials department try to apply this theme, by modifying formulas and replacing components with others that are more sustainable. During their presentation, these new materials, are mostly introduced with the same aspect and touch as the previous ones in an attempt to show that they have the same type of performance. However, the client and the final user want evidence of sustainability. Thus, the following question was posed: is it possible to develop a surface that includes an aesthetic component associated with the theme of sustainability? Inspired in projects already accomplished in incorporation of natural fibers, it is proposed to create the aesthetic component with a link to sustainability through the application of algae and PET (one of the most used plastics in food containers and packaging, such as transparent water bottlers) in plastic components. Thus, the main objectives of the project are to use these residues, which are often removed from the beaches and are not properly recycled, and to create a surface for the interior parts of the car. With the support of TMG Automotive and of open-source information in literature, it was possible, through quantitative explanatory methodology, to extract information to form an investigation guide, and to carry out the necessary tests to develop the product and respond to the defined objectives.